Effects of women with gestational diabetes mellitus related weight gain on pregnancy outcomes and its experiences in weight management programs: a mixed-methods systematic review - He, Jing; Hu, Kaili; Wang, Binghua; Wang, Hui (Frontiers in Endocrinology, 2023)
Introduction: Proper controlling gestational diabetes mellitus (GDM)-related gestational weight gain (GWG) during pregnancy can optimize pregnancy outcomes and improve postpartum glucose homeostasis. This study aimed to explore the existing intervention programs, the effects on pregnancy outcomes, and the experiences of weight management for GDM-related GWG in women with GDM. Methods: This mixed-methods systematic review was retrieved from nine databases. The retrieval time was from the database construction to September 20, 2023, and all studies were published in English and Chinese. The included records used quantitative, qualitative, or mixed methods and reported original studies of weight-related intervention regimens, effects on pregnancy outcomes, and women's experiences and perceptions. This review used a convergent segregated approach to synthesize and integrate research findings from Joanna Briggs Institute (JBI) mixed-methods systematic reviews. Results: There were 16 articles that met the inclusion criteria, and the articles came from seven different countries and included 23,997 women with GDM. The meta-analysis pooled outcomes for the incidence of weight gain exceeding the Institute of Medicine (IOM) recommendations after GDM diagnosis to delivery was 0.31% (95% CI 0.21-0.42). The effectiveness of GDM-related weight interventions in reducing weight gain after GDM diagnosis was supported by quantitative evidence. The GDM-related GWG below the IOM recommendations is a protective factor (OR=0.68, 95%CI 0.48-0.97) for large for gestational Age (LGA), and above the IOM recommendations is a risk factor (OR=1.62, 95%CI 1.15-2.27) for LGA. In addition, no significant statistical significance was found in the pooled outcomes of small for gestational age (SGA). Avoiding excessive weight gain helps to optimize neonatal birth weight, pregnancy outcomes, and maternal blood glucose levels. According to qualitative survey results, some women with GDM experienced weight stigma, and a positive relationship between healthcare providers and GDM women helped in weight management. Conclusions: Following a diagnosis of GDM, weight management interventions positively affected GWG and pregnancy outcomes. In order to improve compliance and safety of weight management in women with GDM, criteria and interventions for weight gain associated with GDM need to be further explored and improved.